Heat and Mass Transport in Modeling Membrane Distillation Configurations: A Review - Olatunji, Samuel O.; Camacho, Lucy Mar (Frontiers in Energy Research, 2018)
Identification and mitigation of challenges associated with membrane distillation (MD) modeling are very crucial to the applicability of MD technology in the industry. Several research studies have been carried out on direct contact membrane distillation (DCMD) modeling because of its simplicity, while other MD configurations have gained little attention. Most studies conducted on MD modeling were achieved based on uniform membrane pore size and pore size distribution assumption. This study exploits the homogeneity of these assumptions to conduct a modeling review for temperature polarization (TP) and concentration polarization (CP), as they apply to MD configurations. TP and CP phenomena have been identified as two of the main challenges to advance MD modeling for further development of MD technology. Their impact is detailed in the heat and mass transfer mechanisms discussed. Thermal conductivity of common hydrophobic commercial membrane materials at different temperatures are presented in this study. The use of optimal operating flow rate, suitable membranes and proper module design are recommended as viable solutions to reduce the effects of TP and CP on permeate flux decay.